Analisis Dinamika Komunitas Warganet Twitter Terkait Diskusi Agama Islam Tahun 2009-2019 - Taufik Edy Sutanto; Fillah Arjuna, Ahmad Salik; Nur Inayah (The Indonesian Journal of Computer Science, 2024)
Twitter, as a popular social media in Indonesia, is a platform for users to form communities and share information, including about Islam. Opinions generated through this platform can change perceptions about the teachings and practices of Islam in Indonesia. This study aims to understand the structure and evolution of the Muslim community on Twitter through an analysis of community dynamics during 2009-2019. The data was transformed into a graph-shaped network and analyzed using two community detection methods: Louvain and Leiden. Content analysis such as n-grams, hashtags and word clouds were applied to identify the topics of the 3 largest communities. Leiden was shown to produce a higher average modularity value: 0.837, compared to Louvain: 0,833. This research provides deep insights into the community dynamics and discussion topics of Islam in Indonesia on social media, which can serve as a basis for policy makers and academics in managing social and religious issues.